Proszę o pomoc! Rozwiąż układ równań metodą podstawiania:

[tex]\left \{ {{3(2x-y)-2(x+4y)=6-10y} \atop {0,5(x-3y)-(4y-x)+8=0}} \right.[/tex]


Odpowiedź :

Odpowiedź:

3(2x - y) - 2(x + 4y) = 6 - 10y

0,5(x - 3y)- (4y - x) + 8 = 0

6x - 3y - 2x - 8y = 6 - 10y

0,5x - 1,5y - 4y + x + 8 = 0

4x - 11y + 10y = 6

1,5x - 5,5y + 8 = 0

4x - y = 6

1,5x - 5,5y = - 8

- y = 6 - 4x

1,5x - 5,5* (6 - 4x) = - 8

- y = 6 - 4x

1,5x + 33 - 22x = - 8

- y = 6 - 4x

- 20,5x = - 8 - 33

- y = 6 - 4x

- 20,5x = - 41 / :(-20,5)

- y = 6 - 4x

x = 2

- y = 6 - 4 * 2

x = 2

- y =  - 2 / - 1)

y =  2

x = 2

y = 2

Szczegółowe wyjaśnienie: